Morphological changes in the experimental treatment of type 2 diabetes with salts of humic acid. - Kovalchuk, Olena; Pedorenko, Kateryna; Kovalchuk, Svitlana (The Ukrainian Scientific Medical Youth Journal, 2021)
The incidence of diabetes is growing steadily, becoming a real epidemic and becoming a great problem not only for medicine but also for society as a whole. Due to the fact that about 90% of all patients are patients with type 2 diabetes. The priority among researchers is to find new treatments for type 2 diabetes. There are a number of articles on the treatment of type 2 diabetes with salts of humic acid. This article highlights the experimental study of the therapeutic properties salts of humate in rats. The data obtained during the study and after the study of morphological changes of target organs (liver, myocard, kidneys) indicate insufficient both protective and therapeutic action salts of humic acid.